2005
DOI: 10.1111/j.1365-2133.2005.06999.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus is associated with human herpesvirus type 7 replication and infiltration of plasmacytoid dendritic cells

Abstract: We conclude that HHV-7 replicates in LP lesions, but not in psoriasis, another inflammatory skin condition. HHV-7 is possibly involved in the pathogenesis of LP. These preliminary data make further research on this topic of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 13 publications
2
53
0
5
Order By: Relevance
“…Viral infections have recently been linked with OLP. Herpes Simplex virus-1 (HSV-1), Cytomegalovirus (CMV), Human Herpes virus-6 (HHV-6) (5, 6), Epstein-Barr virus (EBV) (5,7,8), Human Papilloma virus (HPV) (7) and Hepatitis C virus (HCV) (5,6) are virus types that have been studied in the etiopathogenesis of OLP. The aim of the present study was to assess the prevalence of HSV, EBV and HPV in histologically diagnosed OLP cases and to evaluate whether any specific clinical variants or histopathological features show a higher frequency of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Viral infections have recently been linked with OLP. Herpes Simplex virus-1 (HSV-1), Cytomegalovirus (CMV), Human Herpes virus-6 (HHV-6) (5, 6), Epstein-Barr virus (EBV) (5,7,8), Human Papilloma virus (HPV) (7) and Hepatitis C virus (HCV) (5,6) are virus types that have been studied in the etiopathogenesis of OLP. The aim of the present study was to assess the prevalence of HSV, EBV and HPV in histologically diagnosed OLP cases and to evaluate whether any specific clinical variants or histopathological features show a higher frequency of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, recent evidence suggests a significant role of PDCs in LE pathogenesis [6,7]. Although PDCs have been shown to be increased in all forms of cutaneous LE and lichen planus, their prominence and patterns of distribution in the two diseases were different [6,7,8,9,10,11]. PDCs were constantly more prominent and detected as distinct perivascular and periadnexal clusters in LE, while in lichen planus they were commonly increased in the upper dermis and in the epidermis adjacent to necrotic keratinocytes [6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although PDCs have been shown to be increased in all forms of cutaneous LE and lichen planus, their prominence and patterns of distribution in the two diseases were different [6,7,8,9,10,11]. PDCs were constantly more prominent and detected as distinct perivascular and periadnexal clusters in LE, while in lichen planus they were commonly increased in the upper dermis and in the epidermis adjacent to necrotic keratinocytes [6,7,8,9,10,11]. Recently, Walsh et al [11 ]showed a significant diagnostic value of three criteria pertaining to PDCs (representation of ≥10% of inflammatory infiltrate, arrangement in clusters of ≥10 cells, presence at the dermoepidermal junction, DEJ) in differentiating hypertrophic LE from its mimickers.…”
Section: Introductionmentioning
confidence: 99%
“…Otuz üç hastanın biyopsi örneklerinin değerlendirildiği bir çalışmada, liken planus lezyonlarında lezyonsuz deriye göre anlamlı derecede fazla HHV-7 ile enfekte hücreler izlenmiştir. 34 Ayrıca, nörosarkoidozlu bir hastada serebrospinal sıvıda HHV-7 saptandığı bildirilmiştir. 35 HHV-7 tanısında kullanılan testler ve testlerin değerlendirilmesindeki zorluklar HHV-6'ya benzemektedir.…”
Section: Human Herpes Vi̇rüs-7unclassified